Pengaruh Gaya Kepemimpinan, Beban Kerja Dan Stres Kerja Terhadap Kinerja Pegawai (Studi Kasus Pegawai PPNPN Kantor BPN Kabupaten Malang) - Rendi Muhammad Ainul Yaqin; Ronny Malavia Mardani; Kartika Rose Rachmadi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and analyze the influence of leadership style, workload and work stress on the performance of PPNPN employees at the BPN Malang Regency Office. The sample used in this study were 79 employees using the saturated sample technique. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is the F test and t test. Based on the results of testing the F test the model is qualify goodness of fit, so it is feasible to use for further analysis. Meanwhile, based on the results of the t-test, the leadership style variable has no significant effect on the performance of PPNPN employees at the Malang Regency BPN Office, the variables of workload and work stress have a significant effect on the performance of PPNPN employees at the Malang Regency BPN Office. Keywords : Leadership Style, Workload, Work Stress and Performance Employee